STX2 Promotes Trophoblast Growth, Migration, and Invasion Through Activation of the PI3K-AKT Pathway in Preeclampsia - Li, Yan; Sun, Xian-li; Ma, Chun-ling; Li, Chao; Zhan, Ying; Li, Wen-ting; Li, Can; Wang, Yi-hao (Frontiers in Cell and Developmental Biology, 2021)
Objectives Abnormal trophoblast behaviors during pregnancy contribute to the development of preeclampsia (PE). Syntaxin2 (STX2) has been shown to be a crucial epithelial mediator in numerous diseases. However, the functions of STX2 and the mechanisms underlying its role in PE remain largely unknown. The aim of this study was to explore the role of STX2 on trophoblast biology and unravel the molecular mechanisms that contribute to the development and progression of PE. Materials and Methods We first compared the expression of STX2 in placental tissues from women with PE and women with normal pregnancies. Then, we investigated the role of STX2 on trophoblast proliferation, migration and invasion in HTR-8/SVneo and primary human trophoblast cells by loss or gain of function experiments. In addition, co-immunoprecipitation, pulldown and immunofluorescence assays were performed to investigate the co-localization of STX2 with other proteins, and to help clarify the mechanisms underlying STX2-mediated functions on trophoblasts. Results We demonstrated that STX2 expression was downregulated in placental tissues of women with PE compared with those from normal pregnancies. Loss and gain of function experiments further confirmed a role for STX2 in cell proliferation, migration and invasion in trophoblasts. By co-immunoprecipitation, pulldown and immunofluorescence co-localization assays, we revealed that STX2 selectively interacted with p85, a subunit of PI3K, and directly recruited p85 to the cytomembrane, thereby activating the AKT signaling pathway. We further demonstrated that the AKT activation was abolished by the use of a PI3K inhibitor (LY294002), which negatively affected STX2-mediated functions on trophoblasts. Conclusion All together, our findings point to a crucial role for STX2 in PE progression. Our new insights also suggest that STX2 may be a potential diagnostic tool and a novel therapeutic target for treating PE.